Impact of interdisciplinary learning on the development of engineering students’ skills - Costa, Alexandra (2019)
This paper intends to present an interdisciplinary project carried out in a School of Engineering, and to refer to its effects in the development of students’ skills. This project’s main goal was to present students with an intellectually demanding challenge which implied overcoming the disciplinary barriers thus integrating knowledge to solve the problems they were challenged with. After the project had been concluded, a study was carried out using a qualitative methodology by conducting two focus groups (n = 16). The main goal of this procedure was to get a better perception of (1) how students understood the project; (2) what kind of skills students considered to have developed throughout the project, and (3) the importance they have attributed to this kind of project. The results demonstrate that students are aware of the relevance of the project not only for their education process but also for the development of their skills. The results of the study also reveal that the students involved in the project have been capable of identifying the specific skills that the project work had intended to address and develop.